2018
DOI: 10.3390/ijms19072007
|View full text |Cite
|
Sign up to set email alerts
|

Plant MicroRNAs in Cross-Kingdom Regulation of Gene Expression

Abstract: MicroRNAs (miRNAs) are a class of noncoding small RNAs, which play a crucial role in post-transcriptional gene regulation. Recently, various reports revealed that miRNAs could be transmitted between species to mediate cross-kingdom regulation by integrating into a specific target gene-mediated regulatory pathway to exert relevant biological functions. Some scholars and researchers have observed this as an attractive hypothesis that may provide a foundation for novel approaches in the diagnosis, prognosis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 74 publications
0
37
0
1
Order By: Relevance
“…However, beside these predictions, no study so far has firmly demonstrated the functionality of plant-derived miRNA on the mammalian genome and it is still a matter of debate. 45 In the intestinal lumen, dietary TGs are modified into monoacylglycerol and fatty acids, which are incorporated into micelles and taken up by enterocytes. Once in the enterocytes, monoacylglycerol and fatty acids are re-esterified into TGs and packaged into chylomicrons for secretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, beside these predictions, no study so far has firmly demonstrated the functionality of plant-derived miRNA on the mammalian genome and it is still a matter of debate. 45 In the intestinal lumen, dietary TGs are modified into monoacylglycerol and fatty acids, which are incorporated into micelles and taken up by enterocytes. Once in the enterocytes, monoacylglycerol and fatty acids are re-esterified into TGs and packaged into chylomicrons for secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-species regulation of miRNAs has already been shown in many virus and parasites (6). Early study in 2004 shown that virus could encode miRNAs and regulate host gene expression (19).…”
Section: Discussionmentioning
confidence: 97%
“…Such phenomena are highlighted as the cross-kingdom regulation of plant miRNAs (3). It is believed that these plant-derived miRNAs have roles in human biological processes and disease (6). In 2007, we built the human miRNA disease database (HMDD) (7) and proposed version 2 and 3 in 2014 and this year (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The small RNAs are a diverse class of non-coding regulatory RNAs with important functions by regulating gene expression through targeting the RNA transcripts of endogenous as well as exogenous genes involved in stress response [94,95]. Growing evidence reveals that miRNA-guided regulation of ROS-related genes at the post-transcriptional level is essential for normal growth and development [96], and adaptation to stress conditions including salinity [97,98].…”
Section: Discussionmentioning
confidence: 99%